THE IMPLEMENTATION OF SCIENTIFIC APPROACH TO IMPROVE STUDENTS’ SPEAKING ABILITY - Raflesia, Indah Citra; sinaga, juwita boneka (English Department, University of Riau Kepulauan, Batam,Indonesia, 2019)
Abstract This study aimed to find out whether the scientific approach implementation could improve the students' speaking ability. This study setting was in SMK Pertiwi Batam. This study was a Classroom Action Research (CAR) which using Mixed Method of Sequential Explanatory Designs. The data taken through observation sheets, teacher’s journal, field notes, and speaking tests. The data were categorized of quantitative and qualitative data. And the data would be analyzed by mixing both of the quantitative and qualitative data. This study was conducted in two cycles which each consisted of planning, acting, observing, and reflecting. The outcomes of this study indicated that there was any improvement of students' speaking ability. The mean of pre-test of speaking was 44.35. The mean of speaking project of cycle 1 was 66.08. Then, the mean of speaking project of cycle 2 was 73.33. It indicated that the scores and the mean in second cycle were better than the first cycle. In other words, the students’ speaking ability improved and became better from the first meeting up to the following meeting. In addition, the scientific approach had also been implemented well.Keywords: Scientific Approach, Mixed Method Research